Internalization in Islamic Law Progressive in Criminal Law Changes in Indonesia - Haris Maiza Putra; Hisam Ahyani (Jurnal Ilmiah Al-Syir'ah, 2022)
Indonesia is a state of law related to the disparity in the decisions of different judges in deciding a case, especially in criminal decisions. A more in-depth study is needed, especially in the case of rape, where in rape cases in Indonesia, several judges have sentenced them to death. This study aims to uncover and explore the Internalization of Progressive Islamic Law (Mashlahat) in Amending Criminal Law in the Death Penalty by Judges Against Defendants in Rape Cases in Indonesia. Progressive Islamic Law promoting peace (Mashlahat) can realize legal protection and peace for the people of Indonesia. The approach in this study uses an empirical juridical approach. This research is also normative-legal, qualitative, and uses descriptive methods through literature studies. This research is sourced from various books, international journals, and national journals. The results of the study concluded that 1) Progressive Islamic Law Internalization in Indonesia in changing criminal law can be carried out by changing the law, which can be done through peace (maslahat) by prioritizing Islamic values rahmatan lil 'alamin in developing and incorporating Islamic legal values into the national legal system in Indonesia; 2) the occurrence of changes to criminal law in Indonesia which was decided by this Judge (Criminal Disparity), among others: a) the judge sentenced to life imprisonment; b) the death penalty; c) 12 years in prison; d) Castration punishment; e) 4 years imprisonment; 3) Internalization of Progressive Islamic Law towards changes in criminal law in Indonesia, when a court judge wants to decide his case, for example in a rape case, a decision can be made through the Mashlahat (peace) concept without having to decide the case with a life sentence or up to the death penalty, especially for perpetrators of rape.